Dynamic analysis method of rotating shaft with magnetic pattern - Heng-Sheng Hsiao; Shuo-Wu Shih; Jen-Yuan (James) Chang (AIP Advances, 2017)
Vibration issue in rotating system has existed mostly due to imbalance response of a rotating shaft. In general, accelerometers or eddy current probes are commonly used to measure the shaft’s dynamic changes in form of acceleration and displacement. Originated from coding and operating algorithm of hard disk drive, a method to detect the position error of read head is applied on measuring and analyzing dynamic response of rotating shaft system. By magnetizing the pattern on magnetic medium surrounded on the rotating shaft, analog signal can be acquired to determine the shaft’s axial and radial displacement. In this paper, a method of dynamic measuring on rotating shaft is proposed by using magnetic pattern and validated through calibrated experiments.